From cycling 1.0 and 2.0 to cycling 3.0: The evolution of a sport through science, ethics, and artificial intelligence - Zabala, M. (Journal of Science and Cycling, 2025)
This editorial presents a comprehensive account of cycling`s historical and conceptual evolution from the traditional and empirically-based Cycling 1.0, through the collaborative, ethical and evidence-driven Cycling 2.0 (Zabala & Atkinson, 2012), to a proposed Cycling 3.0 era shaped by artificial intelligence (AI). Drawing on original sources, publications, and later empirical studies, it argues that the sport`s ethical and scientific progression should remain grounded in transparency, collaboration, and athlete education. The Cycling 3.0 paradigm can amplify the benefits of 2.0, provided that its algorithms, data systems, and governance frameworks can respect the humanistic and ethical foundations that rescued cycling from its 1.0 crises.